Application of dexmedetomidine‐remifentanil in high‐intensity ultrasound ablation of uterine fibroids: a randomised study. (30th August 2017) - Fu, X; Huang, F; Chen, Y; Deng, Y; Wang, Z
Abstract : Objective: To compare the effects of dexmedetomidine‐remifentanil with the traditional analgesia and sedation regimen midazolam‐remifentanil during HIFU treatment of uterine fibroids. Design: A randomised controlled trial. Setting: Department of Anesthesia in a single hospital. Population: Patients with uterine fibroids. Methods: A total of 80 patients diagnosed with uterine fibroids and scheduled for selective HIFU treatment were randomly divided into the dexmedetomidine group (the D group) and midazolam group (the M group). At 20 minutes before the HIFU procedure, patients in the D group received a loading dose of 0.8  μ g/kg dexmedetomidine, followed by a continuous intravenous infusion of 0.2  μ g/kg/hour until the end of the operation. Patients in the M group were given a corresponding amount of 0.9% saline. Patients in the M group received a slow intravenous infusion of 0.03 mg/kg midazolam before the procedure, an intravenous injection of 0.02 mg/kg 30 minutes later, another 0.02 mg/kg 60 minutes later, followed by 0.02 mg/kg at 40‐minutes intervals. Patients in the D group were given a corresponding amount of 0.9% saline. During the HIFU procedure, patients in both groups were administered remifentanil at an effect site concentration of 1.0 ng/ml. Sedation and analgesia were rated using the Ramsay Sedation Scale (RSS) and Visual Analogue Scale (VAS) before drug administration (T1), after drug administration but before HIFU (T2), at the beginning of HIFU (T3), 15 minutes later (T4), 45 minutes later (T5), 75 minutes later (T6), and at the end of HIFU (T7). Patient satisfaction score and Steward recovery score survey were conducted 30 minutes after surgery. Main outcome measures: Different effects of the traditional midazolam‐remifentanil regimen and dexmedetomidine‐remifentanil. Results: All patients in both groups underwent a successful HIFU procedure without developing serious complications during the postoperative period. However, the D group reported significantly fewer cases of respiratory depression than the M group during HIFU treatment ( P  < 0.05). The pause during HIFU ablation in the D group was significantly shorter than that in the M group. HIFU ablation intensity, the number of patients with an RSS of 3 or 4 measured at different time points, and the number of patients with an RSS of 3 or 4 measured at arousal were significantly greater in the D than the M group ( P  < 0.05). Likewise, the D group scored significantly higher in the evaluation of patient satisfaction, recovery score, and surgeon satisfaction ( P  < 0.05). Conclusions: Both dexmedetomidine‐remifentanil and midazolam‐remifentanil met the requirements and ensured the safety of HIFU treatment of uterine fibroids. However, compared with the traditional midazolam‐remifentanil regimen, dexmedetomidine‐remifentanil was associated with more stable sedation in patients, more efficient HIFU treatment and higher degree of patient comfort. Tweetable abstract: Dexmedetomidine‐remifentanil is associated with more stable sedation in patients, more efficient HIFU treatment and higher degree of patient comfort than is midazolam‐remifentanil. Tweetable abstract: Dexmedetomidine‐remifentanil is associated with more stable sedation in patients, more efficient HIFU treatment and higher degree of patient comfort than is midazolam‐remifentanil.